2022
DOI: 10.1161/atvbaha.122.317711
|View full text |Cite
|
Sign up to set email alerts
|

KANK4 Promotes Arteriogenesis by Potentiating VEGFR2 Signaling in a TALIN-1–Dependent Manner

Abstract: BACKGROUND: Arteriogenesis plays a critical role in maintaining adequate tissue blood supply and is related to a favorable prognosis in arterial occlusive diseases. Strategies aimed at promoting arteriogenesis have thus far not been successful because the factors involved in arteriogenesis remain incompletely understood. Previous studies suggest that evolutionarily conserved KANK4 (KN motif and ankyrin repeat domain-containing proteins 4) might involve in vertebrate vessel development. However, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…and Amanda Haage et al reported that knockout Talin-1 in drosophila and mice universally lead to defects in integrin-mediated adhesion [ 37 , 38 ]. Zhang et al showed KN motif and ankyrin repeat domain-containing proteins 4 (KANK4) can link vascular endothelial growth factor receptor 2 (VEGFR2) to TALIN-1, resulting in enhanced activation of VEGFR2 and increased proliferation of endothelial cells (ECs) [ 39 ]. Both Talin-1 expression levels and mutation have been associated with tumor progression and metastasis across several types of cancer, including hepatocellular carcinoma, breast cancer, and prostate cancer [ 40 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…and Amanda Haage et al reported that knockout Talin-1 in drosophila and mice universally lead to defects in integrin-mediated adhesion [ 37 , 38 ]. Zhang et al showed KN motif and ankyrin repeat domain-containing proteins 4 (KANK4) can link vascular endothelial growth factor receptor 2 (VEGFR2) to TALIN-1, resulting in enhanced activation of VEGFR2 and increased proliferation of endothelial cells (ECs) [ 39 ]. Both Talin-1 expression levels and mutation have been associated with tumor progression and metastasis across several types of cancer, including hepatocellular carcinoma, breast cancer, and prostate cancer [ 40 43 ].…”
Section: Introductionmentioning
confidence: 99%